2006
DOI: 10.1242/dev.02450
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of telencephalic and eye-field identities inside the zebrafish forebrain territory is controlled by Rx3

Abstract: Anteroposterior patterning of the vertebrate forebrain during gastrulation involves graded Wnt signaling, which segregates anterior fields (telencephalon and eye) from the diencephalon. How the telencephalic and retinal primordia are subsequently subdivided remains largely unknown. We demonstrate that at late gastrulation the Paired-like homeodomain transcription factor Rx3 biases cell specification choices towards the retinal fate within a population of bipotential precursors of the anterior forebrain: direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
114
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 31 publications
8
114
0
1
Order By: Relevance
“…Consistently, the levels of Rx3 mRNA were upregulated fourfold in Six3.2 morphants, whereas those of Foxg1 were threefold lower than those detected in GFP-injected embryos (Fig. 7I).Thus, Six3.2 appeared to counteract the activity reported for Rx3 (Stigloher et al, 2006), and its marked effects on Rx3 and Foxg1 expression pointed to a possible direct regulation. Phylogenetic footprinting of the vertebrate Foxg1 and Rx3 loci identified HNCEs containing putative conserved Six3 BSs (supplementary material Fig.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Consistently, the levels of Rx3 mRNA were upregulated fourfold in Six3.2 morphants, whereas those of Foxg1 were threefold lower than those detected in GFP-injected embryos (Fig. 7I).Thus, Six3.2 appeared to counteract the activity reported for Rx3 (Stigloher et al, 2006), and its marked effects on Rx3 and Foxg1 expression pointed to a possible direct regulation. Phylogenetic footprinting of the vertebrate Foxg1 and Rx3 loci identified HNCEs containing putative conserved Six3 BSs (supplementary material Fig.…”
supporting
confidence: 61%
“…Activation of non-canonical Frizzled receptors and expression of Sfrp1 and Rx3 contribute to define the retinal territory, segregating it from the telencephalon in teleosts (Cavodeassi et al., 2005; Esteve et al, 2004;Lopez-Rios et al, 2008;Stigloher et al, 2006). Our study, showing that Sox2 and Six3.2 alterations always affect the telencephalon more than the retina, has two important implications.First, it suggests that the preponderant role of Sox2/Six3.2 in medaka telencephalic development counteracts the activity of retinal and hypothalamic determinants such as Rx3 (Stigloher et al, 2006). Supporting this interpretation, we show that Six3.2 binds to the regulatory region and directly controls the expression of the telencephalic determinant Foxg1 (Tao and Lai, 1992), providing experimental evidence to support previous suggestions in chick (Kobayashi et al, 2002).…”
mentioning
confidence: 57%
“…Although we found a slight decrease in pax6b expression in meis1-morphant eyes, as estimated by RT-PCR (see Fig. S4C,D in the supplementary material), the early expression of the eye selector genes pax6b and rx2 (Stigloher et al, 2006) seemed unaffected, when observed by in situ hybridization (see Fig. S4A,B in the supplementary material and data not shown).…”
mentioning
confidence: 61%
“…In this line, it is remarkable that 'eye genes' such as Pax6 or Lhx2 are also expressed in other parts of the presumptive prosencephalon at late gastrula/early neurula stages and strongly affect telencephalic development in addition to leading to eyeless phenotypes when they are mutated (Bulchand et al, 2001;Mangale et al, 2008;Monuki et al, 2001;Porter et al, 1997;Stoykova et al, 2000). Rx3 is the only factor reported to segregate very early on the telencephalic and eyefield territories in zebrafish (Stigloher et al, 2006). However, the Rx3 mutation, which leads to an enlarged telencephalon and a lack of retina, also has deleterious effects on the anterior hypothalamus, which is reduced or missing (Stigloher et al, 2006).…”
Section: Why Do Cf First Develop Eyes?mentioning
confidence: 99%
“…Rx3 is the only factor reported to segregate very early on the telencephalic and eyefield territories in zebrafish (Stigloher et al, 2006). However, the Rx3 mutation, which leads to an enlarged telencephalon and a lack of retina, also has deleterious effects on the anterior hypothalamus, which is reduced or missing (Stigloher et al, 2006).…”
Section: Why Do Cf First Develop Eyes?mentioning
confidence: 99%